AN INDICATION OF SEA-AIR INTERACTION THAT AFFECTS THE CLIMATE PATTERN OVER THE MOLUCCAN SEA - Aldrian, Edvin (BPPT, 2002)
Starting with the regional annual cycle of rainfall over Molucca, which follow the sun eclipse movement instead of the common Inter Tropical Convergence Zone (ITCZ) movement, a suspicion of the sea-air interaction driven climate pattern comes up. The empirical study on rainfall â sea surface temperature (SST) relationship clarifies a function of rainfall accumulation to SST. A strong evident on the interaction comes from the result of Ocean General Circulation Model (OGCM). The model shows a surface water intrusion that comes from west Pacific into the north Molucca Sea before it enter the mainstream of the Indonesian throughflow in the north end of the Makasar strait. Most of the throughflow, as shown by the model, come from north Pacific, enter the Makasar strait southward and go into the Indian ocean through the Lombok strait (mostly) and a strait between Flores and Timor island. The intrusion of surface water in north Molucca conserves the warm sea surface temperature and keep a high convective area.Diawali dengan pembagian region berdasarkan pola hujan tahunan di Maluku, yangmengikuti pergerakan tahunan matahari dan bukannya yang biasa yaitu Inter TropicalConvergence Zone (ITCZ), kecurigaan akan adanya interaksi laut udara yang mendorong pola iklim timbul. Studi empiris mengenai hubungan hujan dan suhu permukaan laut menjelaskan fungsi akumulasi hujan terhadap suhu laut. Indikasi kuat adanya interaksi berasal dari keluaran model global sirkulasi laut. Model menunjukkan adanya intrusi arus permukaan dari pasifik barat ke Maluku utara sebelum masuk ke alur utama dari arus lintas Indonesia di ujung utara selat makasar. Sebagian besar arus lintas, sebagaimana dituntukkan oleh model, berasal dari utara, memasuki selat Makasar ke selatan dan menuju ke samudra Indonesia kebanyakan melalui selat Lombok dan sebagian kecil melalui selat antara pulau Flores dan Timor. Intrusi arus permukaan di utara Maluku menjaga kehangatan suhu muka laut dan menjaga daerah konvektif aktif.